Capacity of unreinforced masonry walls in out-of-plane two-way bending: A review of analytical formulations. (December 2020) - Chang, Lang-Zi 常浪子; Messali, Francesco; Esposito, Rita
Graphical abstract: Highlights: A dataset of 46 URM walls in two-way bending was considered. Limitations and drawbacks of current analytical formulations were reviewed. Formulations based on virtual work method best estimate the force capacity of walls. Influence of boundaries, pre-compression and openings needs to be re-evaluated. Influence of material properties, especially torsional strength, requires attention. Abstract: Investigations of post-seismic events show that the collapse of walls in out-of-plane (OOP) two-way bending can be one of the most predominant failure mechanisms for unreinforced masonry (URM) structures. To assess the force capacity of URM walls in OOP two-way bending, various analytical formulations have been developed during past decades. However, the accuracy and the application range of these analytical formulations have been evaluated against only a limited number of experiments. For this purpose, a dataset of 46 testing specimens from 8 international testing campaigns was created and used to evaluate current analytical formulations, namely Eurocode 6 based on the yield line method, Australian Standard AS3700 based on the virtual work method, and two other virtual work formulations related to AS3700. A general comparison shows that within the listed dataset, AS3700 overall provides the most accurate predictions. More specifically, AS3700 is the most accurate assessing walls assumed to be partially clamped and walls with openings. Testing specimens were divided into groups to study the influence of crucial factors, such as material properties, boundary conditions, pre-compression, aspect ratio and openings. However, only in a few cases clear trends were identified from the testing data. Sensitivity studies were carried out to reveal how the analytical formulations assess the influence of the crucial factors on the force capacity of the walls. Results expose drawbacks and limitations of the considered analytical formulations. Eventually, potential directions for improving the accuracy and the application range of the analytical formulations are pointed out.